ASPEK PENDIDIKAN ISLAM PROFETIK (TUJUAN, MATERI, STRATEGI, MEDIA, EVALUASI, LINGKUNGAN) - M. Ulyan (AS-SALAM, 2020)
This article discusses the aspects of prophetic Islamic education. Aspects in Islamic education are essentially a process that knows no age limit. This education is based on the Al-Quran and the Prophet's Hadith, which aims to form collective keshalehan (khaira ummah). This research was conducted using the literature study method. The results of this study indicate that Islamic education should help a Muslim be good, both for himself (shalih linafsihi) and good for others (shalih lighairihi). The prophetic education aspect which is based on the values of the Sirah Nabawiyah teachings is an integration between the components of education which are closely related to one another.